ANALISIS EFISIENSI BIAYA PERBANDINGAN METODE LCL DAN KONSOLIDASI PADA PROSES IMPOR KOMPONEN PT CATERPILLAR INDONESIA DARI CHINA DAN JEPANG - Achsanul Nashir (Majalah Ilmiah Bijak, 2017)
Facing an era of free trade, governments and businesses must continue to increase growth across sectors such as trade, investment, and so forth. Indonesia's economic competitiveness globally in 2013 rose three ratings compared to the previous year. This is also the case in the heavy equipment market, especially PT Caterpillar Indonesia. PT Caterpillar Indonesia is facing increasingly tight competition with other heavy equipment manufacturers, both from domestic and abroad.In this research will discuss trucking, storage, freight, and duty by PT Caterpillar Indonesia in order to save and cost efficiency. The approach used is descriptive qualitative research. The authors also want to lift the phenomenon and obstacles that exist in the implementation of management systems, trying to find a discussion of existing problems and describe the descriptive research results that have been achieved.The data shows that there is a difference in the average cost efficiency of storage compared to LCL method consolidation method by 40.35%. For the difference in average cost efficiency of trucking compared to LCL method consolidation method by 24%. While there is no difference in the average cost efficiency of freight over the LCL consolidation method. Finally there is an overall average cost efficiency difference compared to consolidation method with LCL method of 15.62%.